2011
DOI: 10.7763/ijapm.2011.v1.4
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of h-WO3 and CuWO4 Nanocrystalsas Determined from X-ray Spectroscopy and First-Principles Band-Structure Calculations

Abstract: Abstract-The electronic structure of hexagonal WO 3 and triclinic CuWO 4 nanocrystals, prospective materials for functional electronic devices, has been studied using the X-ray photoelectron spectroscopy (XPS) and X-ray emission spectroscopy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…10 we can find the energy-band dispersion for MnWO 4 at ambient pressure and 10 GPa. Wolframites with unfilled d A 2+ cations present indirect band gaps, 48 top of the valence band remains at the same energy. This is translated into a band-gap increase for the MgWO 4 and a band-gap decrease for the MnWO 4 , which is in agreement with the type of band-gap behavior previously reported for CuWO 4 .…”
Section: Energy-band Dispersionsmentioning
confidence: 97%
“…10 we can find the energy-band dispersion for MnWO 4 at ambient pressure and 10 GPa. Wolframites with unfilled d A 2+ cations present indirect band gaps, 48 top of the valence band remains at the same energy. This is translated into a band-gap increase for the MgWO 4 and a band-gap decrease for the MnWO 4 , which is in agreement with the type of band-gap behavior previously reported for CuWO 4 .…”
Section: Energy-band Dispersionsmentioning
confidence: 97%
“…7 a). The upward movement in the VB position indicates a decrease in the band gap, which results in an increased visible-light absorption range [ 98 ]. However, the composition of the CB is still a topic of hot debate.…”
Section: Ternary Mwo 4 Photocatalysts (M = Bivalenmentioning
confidence: 99%
“…Currently, the scientific studies on the electronic properties of pure and doped CuWO 4 have been mainly focused on the photocatalytic (PC) degradation of organic dyes (Rhodamine B, eosin yellow dye and methylene blue) under ultraviolet and visible light [53][54][55], magnetic [56][57][58][59], photoelectrochemical water splitting [60][61][62][63][64], visible and solar-assisted water splitting [65,66], photoanode for solar water oxidation [67,68], electrical transport [69], and photoluminescence (PL) [24,53,70]. An important point to be considered is that the theoretical studies [16,[71][72][73][74][75], performed by means of ab initio calculations based on the density-functional theory (DFT) for the electronic structure of CuWO 4 crystals, have shown that the conduction band (CB) of this oxide is composed of 3d orbitals (Cu atoms) and 5d orbitals (W atoms), while the valence band (VB) is formed of 2p orbitals (O atoms).…”
Section: Introductionmentioning
confidence: 99%